Wild Panax plants adapt to their thermal environment by harboring abundant beneficial seed endophytic bacteria - Liu, Dong; Lin, Liang; Zhang, Tie; Xu, Qian; Wang, Mulan; Gao, Minghai; Bhople, Parag; Pritchard, Hugh W.; Yang, Xiangyun; Yu, Fuqiang (Frontiers in Ecology and Evolution, 2022)
The seed microbiome of plant wild relatives is a potential reservoir of beneficial traits that potentially improve their host plant resilience to fluctuating environments and pathogenic threats. Herein, we studied the seed microbiome of three species of the medicinal genus Panax (P. vietnamensis, P. japonicus and P. stipuleanatus) collected from seven locations in Southwest China. We used qPCR and metabarcoding high-throughput sequencing to target both endophytic bacteria and fungi. Seed bacterial absolute abundance (1.1 × 109~1.0 × 107 gene copy numbers per gram seed) was substantially higher than that of fungi (7.6 × 105~3.7 × 102). Host plant genotype was the main driver of seed microbiome composition for both bacteria and fungi. Panax growing hypothermal environments significantly shaped their seed endophytic bacterial but not fungal microbiota. The three Panax species’ seeds harbored unique microbes (averaged ~150 amplicon sequence variants, ASVs), sharing only 12 bacterial ASVs (half affiliated to Halomonas) and four fungal ASVs. Network analysis showed that the Panax seed endophytic bacteria tend to form inter-weaved functional modules that are majorly connected by core members from the genus Halomonas, Pseudomonas and Pantoea. These genera have been associated with nutrient cycling, plant, disease suppression, and tolerance to environmental fluctuation. Together, these novel insights may shade light on the ecological strategies of wild Panax plants adaptation to their harsh environment by possessing abundant beneficial seed endophytic bacteria.